Analisis Kemampuan Komunikasi Matematis Ditinjau dari Daya Juang Siswa melalui Penerapan Aplikasi Geogebra - Indri Fitriyaningsih; Lia Yulianah; Denis Julian Dani; Fery Insan Firdaus; Saddam Hussein; Puji Lestari (Universitas Majalengka, 2023)
This study aims to determine students' mathematical communication abilities through the application of the Geogebra application and to determine the level of students' learning abilities through the application of the Geogebra application. This research is a mixed methods research (a combination of qualitative and quantitative) with a sequential explanatory research design. The sample for this research was all students of class X MIPA 2 SMA Negeri 1 Bantarujeg Majalengka Regency for the 2020/2021 academic year, a total of 36 students using a purposive sampling technique. The material being studied is the concept of absolute value with the sub-concept of absolute value inequality. the results of the recapitulation analysis of mathematical communication ability questions that have been filled in by students are 80% of students in the Good category and 20% of students in the Very Good category for learning through the application of the geogebra application. the results of the recap analysis of the fighting spirit questionnaire that had been filled in by the students as a whole (100%) were in the high fighting power category 80% of learning through the application of the geogebra application.